QUBIC V: Cryogenic system design and performance. Issue 4 (1st April 2022) - ; Masi, S.; Battistelli, E.S.; de Bernardis, P.; Chapron, C.; Columbro, F.; Coppolecchia, A.; D'Alessandro, G.; De Petris, M.; Grandsire, L.; Hamilton, J.-Ch.; Lamagna, L.; et al.
Abstract: Current experiments aimed at measuring the polarization of the Cosmic Microwave Background (CMB) use cryogenic detector arrays with cold optical systems to boost their mapping speed. For this reason, large volume cryogenic systems with large optical windows, working continuously for years, are needed. The cryogenic system of the QUBIC (Q & U Bolometric Interferometer for Cosmology) experiment solves a combination of simultaneous requirements: very large optical throughput (∼40 cm 2 sr), large volume (∼1 m 3 ) and large mass (∼165 kg) of the cryogenic instrument. Here we describe its design, fabrication, experimental optimization and validation in the Technological Demonstrator configuration. The QUBIC cryogenic system is based on a large volume cryostat that uses two pulse-tube refrigerators to cool the instrument to ∼3 K. The instrument includes the cryogenic polarization modulator, the corrugated feedhorn array, and the lower temperature stages: a 4 He evaporator cooling the interferometer beam combiner to ∼1 K and a 3 He evaporator cooling the focal-plane detector arrays to ∼0.3 K. The cryogenic system has been tested and validated for more than 6 months of continuous operation. The detector arrays have reached a stable operating temperature of 0.33 K, while the polarization modulator has operated at a ∼10 K base temperature. The system has been tilted to cover the boresight elevation range 20°-90° without significant temperature variations. The instrument is now ready for deployment to the high Argentinean Andes.